A comparative analysis of trade in metallurgical products in 2009 - 2013. Case study: Romania vs. Croatia - C. I. Răbonţu; A. G. Babucea; L. Paliu-Popa; A. Bălăcescu (Metalurgija, 2015)
Metallurgy is a domain of the secondary sector, which represented for years in Romania, as in other former Communist countries, a very important activity for gross domestic product and employment. Today, many enterprises which were representative in Romania for the metallurgical industry long ago are targets of the sellers of scrap metal, the scrap metal trade representing a segment that has gained momentum in recent years. Croatia, as a member country of the EU has a special contribution in the trade with metallurgical products and we have proposed in this paper to identify which is the level of international trade with metallurgical products of Romania and Croatia, which included a comparison between these countries. For this aim we’ll use the data provided by Eurostat and World Trade Organization (WTO).